2022
DOI: 10.3233/jad-220227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of Microglia Enhances Proinflammatory Cytokine Release through EphA2/p38 MAPK Pathway in Alzheimer’s Disease

Abstract: Background: The activation of microglia and neuroinflammation has been implicated in the pathogenesis of Alzheimer’s disease (AD), but the exact roles of microglia and the underlying mechanisms remain unclear. Objective: To clarify how the metabolic reprogramming of microglia induce by amyloid-β (Aβ)1-42 to affect the release of proinflammatory cytokines in AD. Methods: MTS assay was used to detect the viability of BV2 cells treated with different concentrations of Aβ1-42 for different periods of time. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Glycolysis can regulate Aβ 1–42 ‐induced cell inflammation through the p38MAPK signaling pathway (X. Ma et al, 2022). The levels of glycolysis and p‐p38MAPK proteins in the brains of the mice were detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycolysis can regulate Aβ 1–42 ‐induced cell inflammation through the p38MAPK signaling pathway (X. Ma et al, 2022). The levels of glycolysis and p‐p38MAPK proteins in the brains of the mice were detected.…”
Section: Resultsmentioning
confidence: 99%
“…Glycolysis can regulate Aβ 1-42 -induced cell inflammation through the p38MAPK signaling pathway (X. Ma et al, 2022). The results showed that Fut and PK significantly reduced the levels of HK II, p-p38MAPK proteins, LD, and the levels of IL-1β, IL-6, and TNF-α in the brain and serum of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] AD PRS was associated with a different lipid class, which are the plasmalogen phosphatidylethanolamines. 43,44 The protein EFNA2 45 was associated to both MCI converter and AD PRS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly APOE and MCI conversion status were correlated to PCSK7 and sphingomyelins SMs have been previously associated with cognitive progression in AD [41-43]. Furthermore, the integration of AD PRS showed that phosphatidylethanolamines [44, 45] and EFNA2 [46] were associated to both (MCI converter and AD PRS), with potential as early targets.…”
Section: Discussionmentioning
confidence: 99%